INTEGRASI NILAI AKHLAK DALAM PENDIDIKAN BUDI PEKERTI (Studi Tentang Karakter Tanggung Jawab dan Disiplin Siswa di SMP N 5 Kota Bengkulu) - Nur Janah, Nuri; Zubaedi; Suradi, Ahmad (JPT : Jurnal Pendidikan Tematik, 2020)
The integration of moral value in character education is moral values regarding the character of the responsibility and discipline of the student. In the implementation of the integratation of moral values regarding the character of responsibility and discipline of students at SMP N 5 Bengkulu City it self, it is not entirely good, for example, there are still some students who are still stubborn about the rules at school, such as students who do not go to school on time and do not do the assignments from the teacher. Skipping school, not wearing a uniform according to school rules, and so on. The objectives of this study are: 1) To find out how the steps in planning the integration of moral values in character education are; 2) To find out how to implement the learning of moral values and integration in character education; 3) To find out how th learning out comes are integrated in character education the type of reaserch used in this reaserch is field reaserch, namely by direct reaserch in the field to obtain data and information and data sources. The results of the analysis carried out, it can be said that: 1) The integration of character education in character education learning at SMP N 5 Bengkulu City is contained in the RPP, the values are integration in the RPP komponen which include: core competancies, and attitudes: 2) The integration of character education in the implementation of learning is carried out the learning process both at the stage of implementing this activity from the introduction, core, and closing; 3) The integration of character education in the results of th evaluation of character education at SMP N 5 Bengkulu City through the provision of oral an non-verbal test.